Professor Emérito José Luis Bado: 1903 - 1977 - García Novales, Jorge (Cirugía del Uruguay, 1978)
On December 19 of last year, the National Medicine lost one of its most important personalities. With him, the man who made the history of Orthopedics and Traumatology of Uruguay disappears, born in the 30s and to which his virtuous scientific method as well as his tenacious desire for perfection, gave characteristics of noble lineage in its development.